The Role of the Behavioral Immune System in the Expression of Short and Long-Term Orientation in Young Chilean Men During the Covid-19 Pandemic - Fajardo-Cuevas, G (BioMed Central Ltd, 2025)
Introduction: The COVID-19 pandemic drastically changed people s lives. It had consequences at the individual and social level. The behavioral immune system predicts that when faced with the risk of contagion from pathogens, people tend to reduce their sociality, especially sociosexuality. We examine this prediction by evaluating decreases in the pandemic of the different dimensions of sociosexuality of young men (i.e., short and long-term mating orientation, sexual desire, and sociosexual behavior) and considering their relationship status (single or paired). Methods and materials: We compared data from two cross-sectional studies carried out in the laboratory with convenience sampling methods in the pre-pandemic period (in the years 2016 and 2018 with a sample size of N = 463) and pandemic (face-to-face panstudy N = 234,data online, N = 182), considering possible differences between samples of the same period. We reached an N = 879 young men who answered a sociodemographic questioarticipants answered a sociodemographic questionnaire that inclnnaire and the Multidimensional Sociosexual Orientation Inventory. To test our predictions, we fitted general linear models. Results: Results point to a significant decrease in long-term mating orientation in paired and single men, but only when compared with the pandemic face-to-face study. In addition, no differences were found for short-term mating orientation. For sociosexual desire (i.e., sexual fantasies), we found a reduction in single pre-pandemic individuals to be compared with the sample of pandemic online study. Finally, we found a decrease in sociosexual behavior (i.e., number of partners in the last year) between pre-pandemic samples and the pandemic itself, regardless of their relationship status and samples inside of each period. In addition, we carry out analyses with a reduced sample to re-test our predictions based on the perception of contagion risk (measured by a survey from OMS). Conclusion: We find changes are maintained at the level of sociosexual desire and sexual behavior but mainly in those individuals with a greater perception of the risk of contagion. The hypotheses derived from the behavioral immune system regarding the decrease in sociosexuality in a context of risk of contagion by pathogens, as was the case in the initial period of COVID-19, are corroborated only in terms of desire and behavior, which suggests a certain stability in attitudes i.e., the menace of contagion modifies proximal aspects of sociosexuality, such as fantasies and behavior, but has no apparent effect on the calibration of the predisposition of individuals to varying levels of commitment in sexual relationships. These findings will allow us to understand better how the dimensions of sociosexuality (i.e., fantasies, attitudes and behavior) are affected when there are contexts of high risk of contagion, such as COVID-19. These findings will allow us to understand better how sociosexuality is affected when there are contexts of high risk of contagion, such as COVID-19. © The Author(s) 2025.